Student Satisfaction in Private and Public Universities in Bangladesh - Quamrul H Mazumder (International Journal of Evaluation and Research in Education (IJERE), 2013)
To compare and contrast the quality of higher education in public and private universities of Bangladesh, a study was conducted, to evaluate student satisfaction in these institutions. The study used a modified Noel-Levitz student satisfaction survey, consisting of twenty two questions which measured student satisfaction levels in four different areas: faculty, curriculum, resources, and campus environment. The survey also measured the students’ overall level of satisfaction with the institution. Data collected from different private and public universities showed overall satisfaction level to be higher among private university students than public university students.  The data also indicated that students from private universities are more satisfied than those of public universities. Finally, comparison of data from male and female students showed higher level of satisfaction among female students.DOI: http://dx.doi.org/10.11591/ijere.v2i2.2060